Gemeinschaftliches Wohnen und selbstorganisiertes Bauen - Holm, Andrej; Laimer, Christoph (TU Wien Academic Press, 2021)
Cohousing and cooperative building offer new solutions to contemporary housing challenges. For years, building collectives and housing projects in many countries have gained experience in cooperative planning, developed new forms of housing, and experimented with unconventional forms of communal housing. Housing initiatives, in particular, make use of cooperative planning processes, non-profit oriented management, and collective responsibility in developing and implementing new forms of cohousing. This publication seeks to show how niches within the capitalist system can be utilized and what alternative approaches exist. For this reason, in addition to contributions on the topics of housing and building, contributions relating to commons, solidarity economies, property, decommodification, and alternative funding methods are also included. This publication arose within a TU Wien fellowship on the topic of "New Social Housing".